PENGEMBANGAN LKPD MATEMATIKA BERBASIS PENGUATAN PENDIDIKAN KARAKTER KELAS IV SEKOLAH DASAR NEGERI 2 KALIJAGA TIMUR - Musabihatul Kudsiah; Arif Rahman Hakim; Muh. Yazid; Ardi Sri Lestari (SIGMA, 2023)
This study aims to develop a Mathematics Student Worksheet (LKPD) based on character education strengthening using the ADDIE model research design which consists of 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. This research was conducted on fourth grade students with the number of respondents being 20 students. This research and development instrument uses a validation sheet, and student response questionnaires. The results of the material expert validation test with a total score of 62 and are in the range of X scores > 58.74 with the "very good" category. The results of the display expert validation test with a total score of 48 and are in the score range of 44.2 < X 54.6 with the "good" category. The results of the student response questionnaire on the feasibility of using the Mathematics Student Worksheet (LKPD) based on strengthening character education developed obtained a score of 218 obtained from the number of "Yes" points and the percentage of the overall components reached 83% in the "good" category. So it can be concluded that the Mathematics Student Worksheet (LKPD) based on strengthening character education is valid and effective to be used as teaching material in character building in schools.